Lethal gastric hemorrhage from a caliber-persistent artery of the antrum - a branch of the right gastric artery - Gurzu, S (SOCIETY OF "FRIENDS OF HIPPOKRATIA JOURNAL", 2014)
AIM: To present a rarely diagnosed case of gastric Dieulafoy lesion. DESCRIPTION OF CASE: A 62-year-old male was hospitalized with hematemesis. Laparoscopic ligature of two gastric ulcers located in the antrum was performed but the upper gastrointestinal bleeding was not stopped. The patient was transferred to another surgical clinic and he underwent an emergency abdominal laparotomy with re-suture of gastric ulcers. Considering his general condition and another recurrent bleeding, he was transferred to our hospital and a total gastrectomy of necessity was performed. The patient died four days after surgery because of sepsis. At autopsy, we identified diffuse peritonitis, hypertrophic cardiomyopathy and chronic pancreatitis with expanded fibrotic areas. Histological examination of the surgical specimen showed oversized tortuous vessels in the gastric submucosal layer with expansion into mucosa. Some of the vessels presented acute and/or organized thrombi with recanalization, in the others, lipid-rich atherosclerotic plaques were observed. Based on these criteria, the ‘caliber-persistent artery’, also known as ‘Dieulafoy’s lesion’, was diagnosed. CONCLUSION: Dieulafoy’s lesion should be suspected in every case of gastrointestinal bleeding in both adults and children.